Aspectos nutritivos de alguns peixes da Amazônia - Rocha, Yolanda Rebelo da; Aguiar, Jaime Paiva Lopes; Marinho, Helyde Albuquerque; Shrimpton, Roger (Acta Amazonica, 1982)
The eleven species of fish most consumed in Manaus in 1973-74 were analyzed for humidity, ash, protein, fat, energy and zinc. Carnivorous fish such as Tucunaré, Pirarucú and Pescada were found to be lean whereas Pacú, Sardinha, Curimatã, Matrinchã and Branquinha were found to be fatty. All of the fishes were high in protein, with protein energy ratios greatly in excess of the recommendations. Zinc energy ratios were only high in the lean, carnivorous fishes, which arc the most expensive and sought after in the local market. The herbivorous, and omnivorous fishes, with high fat contents, had zinc energy ratios below recommended levels. The possible importance of these findings are discussed.